Illegal, unregulated and unreported fishing impacts: A systematic review of evidence and proposed future agenda. (May 2022) - Temple, Andrew J.; Skerritt, Daniel J.; Howarth, Philippa E.C.; Pearce, John; Mangi, Stephen C.
Abstract: Illegal, Unreported and Unregulated (IUU) fishing is a global phenomenon occurring across all fishery types, sectors and geographies. In order to successfully address IUU fishing, fisheries policies, regulations, and management strategies, as well as subsequent monitoring, control and surveillance activities, must be supported by an appropriate evidence base at relevant spatial-temporal scales. Here we present a systematic review of IUU fishing and its impacts at global, and case study regional (Europe and the North East Atlantic) and national (UK) levels in order to determine the extent to which IUU fishing is understood and to identify priority information gaps which undermine current management efforts. The economic and environmental impacts of IUU fishing are well established, as are a wide range of implicit but more difficult to quantify social impacts. However, the amount of public money being spent on combatting IUU fishing is likely at least an order of magnitude lower than the cost of the activities themselves. Data at regional and particularly national levels are often at too low a resolution to provide sufficient evidence capable of supporting effective policy and regulatory actions to address IUU fishing. A contemporary and more granular understanding of IUU fishing is therefore required. We propose a four-step research agenda to improve the understanding of IUU at relevant national spatial-temporal scales and from which to make effective, evidence-based actions: (1) defining intent and goal-setting, (2) risk assessment and prioritisation, (3) estimation of volume, costs and impacts, and (4) economic appraisal of policy and regulatory reform.